Former Olympians had remained on high bone mineral density for a long period: Consecutive checkup of the 1964 Tokyo Olympic Japanese contestants for over 50 years - Hoshikawa, A.; Nakajima, K.; Okuwaki, T.; Hangai, M.; Aono, H.; Ishizuka, S.; Morioka, Y.; Itou, S.; Kawahara, T. (Bone, 2024)
Introduction We performed consecutive checkups of the 1964 Tokyo Olympic contestants every 4 years for 50 years. This study evaluated bone mineral density (BMD) and its related factors in former Tokyo Olympic athletes.